Association study of common variants within the G protein‐coupled receptor kinase 6 gene and schizophrenia susceptibility in Han Chinese. (3rd December 2013) - Tang, Wenxin; Cai, Jun; Yi, Zhenghui; Zhang, Yi; Lu, Weihong; Zhang, Chen
<x xml:space="preserve">Abstract</x> In this study, we examined whether common variants in the G protein‐coupled receptor kinase 6 gene (GRK6) confers susceptibility to schizophrenia in Chinese. We genotyped two common variants in 697 schizophrenia patients and 563 healthy control subjects. No significant difference in either allele or genotype comparisons between the case and control groups was found. Our results imply that GRK6 may not play a role in the pathophysiology of schizophrenia among Han Chinese. Copyright © 2013 John Wiley & Sons, Ltd.